LEAD-LAG AND RELATIONSHIP BETWEEN MONEY GROWTH AND INFLATION IN TURKEY: NEW EVIDENCE FROM A WAVELET ANALYSIS - TURSOY, Turgut; MAR’I, Muhammad (Theoretical and Practical Research in Economic Fields, 2020)
The study investigates the relationship between money supply and inflation and Turkey by employing wavelet analysis, mainly continuous wavelet analysis, cross wavelet transforms and wavelet coherence and phase-difference, for the period from 1987 to 2019. Our main finding confirms the modern quantity theory of money about the existence of a relationship between inflation and money supply in the short-run and long-run, and also confirms the traditional quantity theory of money about the existence of a relationship in the long run. The phase difference confirms the existence of a bidirectional relationship between money supply and inflation. The result is consistent with both the traditional quantity theory of money in the long run and the modern quantity theory of money in the short-run and long-run in terms of the existence of a relationship between money supply and inflation.